ANALISIS KELAYAKAN EKONOMI DAN KEUANGAN USAHA IKAN LELE ASAP DI PEKANBARU - Indo Yama Nasarudin (ETIKONOMI, 2013)
This research is to analyze the feasibility of economic and financial on smoked catfish business in Pekanbaru. The methods analysis that used in this research are B/C ratio, NPV, payback period, profitability index, and IRR. Economic Performance for business of smoked lele fish was very good for marketing aspect and good enough for production, management and human resource aspect. While seen from finance aspect assess the Benefit cost ratio (BCR) equal to 1,39, Value of Payback Period is 2,44 years,  below time specified 10 years. Positive valuable Net Present Value equal is Rp 739.508.134, Value of profitability index equal to 6,35. Rate of return (IRR) equal to 53,09% Pursuant to measurement financial as a whole indicate that the effort competent poultry to be continued.DOI: 10.15408/etk.v12i2.1915